1980
DOI: 10.1046/j.1537-2995.1980.20480260281.x
|View full text |Cite
|
Sign up to set email alerts
|

Retention of HLA Antigens on Previously Frozen Human Platelets

Abstract: Recent technical achievements allow satisfactory cryopreservation of human platelets that, after thawing and washing, maintain functional viability for therapeutic use. We have now demonstrated that such previously frozen platelets retain full HLA antigenic activity in spite of the combination of freezing, thawing, and washing procedures and the presence of the surface-active cryopreservative DMSO. Platelets stored at 4 C without DMSO and previously frozen platelets from the same donors were tested in parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Schiffer & Young (1983) have tried different methods of platelet preservations and found that liquid suspension in normal saline may still be suitable for platelet crossmatching after one year of storage. Nevertheless, one study negates reduction of HLA antigens after freezing, thawing and washing (Pollack et al 1980). Our study found that virtually all the frozen platelets could retain their antigenicity within one month.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Schiffer & Young (1983) have tried different methods of platelet preservations and found that liquid suspension in normal saline may still be suitable for platelet crossmatching after one year of storage. Nevertheless, one study negates reduction of HLA antigens after freezing, thawing and washing (Pollack et al 1980). Our study found that virtually all the frozen platelets could retain their antigenicity within one month.…”
Section: Discussionmentioning
confidence: 51%
“…It has been noted that the expression of HLA antigen on platelets is variable (Schiffer, O'Connell & Lee 1989, Aster et al 1977). Nevertheless, one study negates reduction of HLA antigens after freezing, thawing and washing (Pollack et al 1980). We also observed that the HLA antigens could be preserved and detectable for one month.…”
Section: Discussionmentioning
confidence: 58%
“…However, to function successfully, stored platelet samples must be available on the HLA-typed donors to be used for crossmatching. There are a variety of techniques available to store platelets, but, with many, antigen reactivity is lost over time (61)(62)(63)(64). In addition, to prepare and store platelet samples on a large number of donors is a time-consuming and costly endeavor.…”
Section: Platelet Crossmatch Testingmentioning
confidence: 99%
“…Although HLA-A,B,C antigens on platelets have a varia ble expression in relation to lymphocytes [Colombani et al, 1971;Liebert and Aster, 1977;Mueller-Eckhardt et al, 1978, 1980aSzatkowski and Aster, 1980], they lend themselves to HLA typing and antibody screening [Colombani et al, 1971 ;Svejgaard and Kissmeyer-Nielsen, 1970;Heinrich and Mueller-Eckhardt, 1971 ;Degos et al, 1975], Due to their lack of D-related HLA antigens, they are also widely used to absorb HLA-A,B,C antibod ies from sera containing HLA class II antibodies. For these purposes, platelets can be stored for many months at 4°C, or in the frozen state without loss of HLA-A,B,C antigenicity Pollack et al, 1980]. Furthermore, HLA-incompatible platelets have been shown to have a shortened survival time when transfused into HLA-immunized patients.…”
Section: Adsorption In Vivomentioning
confidence: 99%